Pengaruh Variasi Temperatur Proses Austempering Terhadap Mikrostruktur dan Sifat Mekanik Baja Armour - Slamet Sutjipto; Ilham Azmy; Destri Muliastri; Devi Eka Septiyani Arifin (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Armour steel is a medium-carbon steel which is widely used in military and defense industries owing to its ability to protect from projectile and bullet pressure. However, this armour steel still posses mechanical limitation aspect, thus it is needed to engineer for improvement. Therefore, the aim of this research is to undergo mechanical properties engineering by using heat treatment method of austempering within temperature variations of 200, 250, 350, 450, and 500 oC . Experimental results show that austempering process affected to fraction quantity of phase and microstructure of ferrite, pearlite, and bainite. Armour steel resulted by austempering process in temperature 500 oC depicts microstructure transformation and mechanical properties improvement significantly. Microstructure transformation along with proportional fraction volume phases of upper bainite, ferrite, and pearlite highly beneficial to increase impact strength dan ductility of armour steel. Thereby, armour steel resulted by austempering process in temperature 500 oC has thoroughly increased its mechanical properties which capable to be applied in military and defense industries.